Iatrus during the 4th century CE in the context of historical development. Some preliminary considerations on the interpretation of excavation findings - Wachtel, Klaus (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the development of the settlement of Iatrus in the 4th century AD in the context of historical transformations. The research problem concerns the interpretation of archaeological data and their correlation with written sources. The aim of the work is to reconstruct the stages of development of the settlement and explain its transformations. The author applies archaeological and comparative analysis. The most important results indicate three stages of development of Iatrus: an initial phase at the beginning of the 4th century, a transformation of the settlement in the second half of the 4th century, and later stages up to the 6th century. In the second phase, urban changes and rebuilding of the earlier structure occurred. The research also indicates the absence of an earlier settlement at this location and the military significance of the site. The conclusion is that the development of Iatrus reflects broader military and settlement transformations on the frontier of the empire.